FAKTOR RISIKO KEJADIAN GASTRITIS PADA PASIEN POLRI DI WILAYAH KERJA KLINIK POLRES MUNA TAHUN 2022 - Melly Erdana; La Ode Muhamad Sety; Irma Irma (Endemis Journal, 2022)
Gastritis in police patients in the working area of the Muna Police Clinic still has a high prevalence, which is still the top 5 main diseases in 2019-2021. Factors that trigger gastritis include: diet, socioeconomic, family history of gastritis, alcohol consumption, smoking, stress, and drugs. Gastritis can attack all levels of society from all levels of age and gender. This study aims to determine the risk factors for eating regularity, type of food, stress and smoking on the incidence of gastritis in Polri patients in the working area of the Muna Police Clinic in 2022. The type of research used was observational analytic with a Case Control Study design. The population in this study were all patients who checked themselves at the Muna Police Clinic from January to August 2021. The sample in this study amounted to 76 samples (38 cases and 38 controls). Sampling used two approaches, namely random and non-random sampling. The results showed that the risk factor for gastritis, namely regularity of eating, obtained p-value = 0.000, OR = 37.593, while the non-risk factor for gastritis, namely stress, obtained p-value = 0.723, OR = 1.288. The police are expected to be more aware of the factors that cause gastritis, and more importantly know how to prevent gastritis as early as possible, so that complications do not occur. And the police should be able to maintain health and maintain a good and healthy diet with balanced nutrition.